Variation in fecundity among different genotypes of cod (Gadus morhua L.) - Lovísa Ólöf Guðmundsdóttir 1986- (2010)
The cod stock around Iceland consists of separate components characterized by different migration behavior, phenotype and genotype. Two kinds of behavior types, deep water behavior and shallow water behavior, have been observed and a significant difference in otoliths indicates an elongated separation between the two groups. These behavior types are connected to the Pan-I locus as Pan-IAA fish mostly exhibits shallow water behavior, Pan-IBB fish mostly exhibits deep water behavior but Pan-IAB fish both behavior types. Ovary and oocyte samples from Icelandic cod Gadus morhua were collected from eight locations south of Iceland in spring 2009. We used the auto-diametric fecundity method to evaluate the potential fecundity of cod, determined the genotype at the Pan-I locus and compared fecundity for different genotypes. We did not find a significant difference between genotypes but our results still suggest a possible variance in fecundity that needs further investigation.